Некоторые особенности проявления оценочности в американском политическом дискурсе (на материале инаугурационной речи Б. Обамы) - Горина, С.Л.; Татарникова, И.В. (Культура народов Причерноморья, 2014)
В статье рассматриваются вопросы, касающиеся особенностей выражения категории
оценочности в политическом дискурсе, а также проанализированы рекуррентные оценочные маркеры,
характерные для политического выступления президента США Барака Обамы. В ходе исследования
выявлены следующие оценочные средства воздействия на аудиторию: ярлыки, использование цифр,
оценочные слова, отрицание. В статті розглядаються питання, які стосуються особливостей реалiзацii категорії
оцінковості у політичному дискурсi, а також проаналізовані рекуррентні оціночні маркери, які є
типовими для політичного виступу президента США Барака Обами. У ході дослідження було виявлено
такі оціночні засоби впливу на аудиторію: ярлики, використання цифр, оціночні слова, заперечення. Political discourse is the key notion of political linguistics. It represents a special kind of discourse
which is aimed at gaining and withholding political power. This kind of discourse embraces all the speech acts
which are used in political discussions and is based on time-honoured rules of public politics which have been
implemented in practice. The article deals with problems related to the linguistic manifestation of the category of
evaluation in present-day political discourse represented in speeches of American politicians. The findings cover
the analysis of а recurrent evaluation markers which are typical for the first inaugural speech of the US
President Barack Obama and which are conducive for the exteriorization of the positive image of this popular
politician. In the course of the investigation the following evaluational means of influence on the audience have
been detected: tags, the usage of digits, evaluation words, negation.